US Pivot and Stability in the Asia Pacific Region - Angel Damayanti (Global Strategis, 2015)
The US rebalancing strategy in Asia Pacific confirms the importance of AsiaPacific region particularly for the US and her interest. A rapid economicdevelopment in Asia Pacific states coupled with security dynamics thatpotentially triggers instability in the region have become driving factors forthe US involvement in the region. The US (re)-existence as well as her activeengagement obviously gives rise to multiple responses and leads to negativeperception. This article perceives that the US pivot in Asia Pacific including thestrengthening of US influence in the region might provoke tension particularlywith China. Nonetheless, a common and mutual interest in economic andsecurity has forced both states to self-restrain and develop strategicpartnership, which is essential to achieve their common goals together withother Asia Pacific states. To understand the US strategy and the impact of thestrategy, this article analyzes the US official documents as well as otherrelated states’ documents, and using the “post-modern states” approach toexplain the implication of US military strategy